Banking Locker System with Odor Identification & Security Question Using RFID & GSM Technology - Jasmin, M.; Philomina, S.; Virgin, G. Angelo (International Journal of Psychosocial Rehabilitation, 2018)
— This paper portrays Banking Locker Security framework with Odor ID, Security Questions utilizing RFID and GSM innovation which can be utilized as a part of banks, organizations and at individual secured places. Just unique record holder can utilize his locker. This framework utilizes Odor ID, Security address strategy, RFID innovation and GSM innovation which makes it more secured than whatever other framework. The framework is more secured as 4 stages are required for check. RFID tag is confirmed utilizing RFID innovation, then legitimate individual needs to answer the security address utilizing Security address programming system and it ought to be same as that of put away (at first amid record opening),then the substantial individual gets message in his versatile utilizing GSM innovation and needs to sort secret key from his portable and keypad of locker, both passwords ought to match to open the entryway of the locker, and after that scent distinguishing proof will be done, the smell example ought to coordinate with the scent design put away in the microcontroller.